Effect of Crude Glycerol from Biodiesel Production on the Performance and Anaerobic Metabolism of Catalysts in a Glycerol Oxidizing Microbial Fuel Cell - Sivell, Jamie-lynn (Université d'Ottawa / University of Ottawa, 2014)
Use of waste glycerol as fuel in microbial fuel cells (MFCs) would result in the production of valuable metabolites and electricity, to the benefit of biodiesel operations. In this research, the effect of salt and other compounds found in waste glycerol from biodiesel production on the metabolism and performance of three cultures (Escherichia coli W3110, Propionibacterium freudenreichii ssp. shermanii and mixed culture AR2), used as anodic catalysts in an MFC was studied. MFC experiments were performed in parallel with serum bottle fermentations to allow for comparison of glycerol consumption and metabolite yield. The effect of salt content on the performance of all three cultures was positive in most cases and negligible in others. Using waste glycerol with an increased concentration of other compounds (other than salt) only reduced the performance of AR2, however an inhibitory effect on the rate of glycerol consumption was observed with both AR2 and P. freudenreichii ssp. shermanii. For all strains, the rate of glycerol consumption was slower in MFCs than in fermentations as a result of the electrochemical environment; the yield of various metabolites also differed.
Keywords: Microbial fuel cell; Glycerol; Biodiesel